Peranan Pendidikan Agama Dalam Menyelesaikan Problem Rumah Tangga - Jauhari, Jauhari; Candra, Andi; Afriani, Kinaria; Merita, Enni (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2025)
The increase in divorce cases indicates the need for more effective interventions to strengthen family bonds. Islamic religious education also has an important role in strengthening family resilience and preventing divorce in society. A deep understanding of Islamic teachings can provide a strong spiritual foundation for married couples in living married life. The morals and ethics taught by Islam provide a solid foundation for harmonious family relationships. This research uses literature study, which means that this research looks at the theories, concepts and provisions of Sharia in the research made by the author. The results of this research show that Islamic religious education is very important in maintaining family resilience and can prevent divorce in solving household problems.